Artificial Intelligence in Healthcare sector: Understanding Drivers and Future Prospects (International Journal of Food and Nutritional Sciences, 2022)
This research tries to study drivers of Artificial Intelligence (AI) with respect to healthcare sector. As a theoretical underpinning, Unified Theory of Acceptance and Use of Technology 2(UTAUT2) was validated. Data was collected from 600 healthcare professionals using AI architecture in their organizations and was analyzed using Structural Equation Modelling (SEM). The results of the study indicated all the drivers has a significant positive impact on behavioural intention except hedonic motivation. This indicates that adoption of AI has more of utilitarian orientation rather than hedonic orientation. Further BI depicted a strong influence on actual usage of AI systems in healthcare segment. Using this information and related facts as a foundation, healthcare organisations can develop effective artificial intelligence enablement practises that consistently lead to the development, design, deployment, and dissemination of appropriate, effective, and sustainable artificial intelligence enabled solutions.